2001
DOI: 10.1212/wnl.57.5.845
|View full text |Cite
|
Sign up to set email alerts
|

Ingested IFN-α

Abstract: This trial showed no benefit based on the primary outcome measure. Because changes were detected in immune response and post hoc analysis suggested that a smaller dose could have an effect, IFN-alpha may deserve further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…Most importantly, we have also demonstrated that IFN-, in contrast to IFN-␣ or IFN-␤, does not promote secretion of IFN-␥, an attractive feature of this type I IFN, which could also contribute to the different clinical observations made in these two studies. This key pharmacodynamic difference between IFN-and IFN-␣ should be considered in view of the results from a recent pilot MS trial using oral IFN-␣ that suggested that oral IFN-␣ may not be effective in treatment of relapsing-remitting MS (23). In addition, patients in that trial received either 10,000 or 30,000 U of IFN-␣.…”
Section: Resultsmentioning
confidence: 99%
“…Most importantly, we have also demonstrated that IFN-, in contrast to IFN-␣ or IFN-␤, does not promote secretion of IFN-␥, an attractive feature of this type I IFN, which could also contribute to the different clinical observations made in these two studies. This key pharmacodynamic difference between IFN-and IFN-␣ should be considered in view of the results from a recent pilot MS trial using oral IFN-␣ that suggested that oral IFN-␣ may not be effective in treatment of relapsing-remitting MS (23). In addition, patients in that trial received either 10,000 or 30,000 U of IFN-␣.…”
Section: Resultsmentioning
confidence: 99%
“…Entry criteria included newly diagnosed type 1 diabetes mellitus (within 1 month of diagnosis) (n 5 10) (ages [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Pediatric and adult endocrinologists diagnosed patients with type 1 diabetes mellitus from the inpatient and outpatient registries of the University of Texas Houston Medical School according to American Diabetic Association (ADA) criteria (fasting blood sugar [FBS] .125; 2 h postprandial .200).…”
Section: Subjectsmentioning
confidence: 99%
“…(8) Ingested recombinant human IFN-a (rHuIFN-a) was nontoxic and was a BRM in humans in a phase I clinical trial in relapsing-remitting multiple sclerosis (RRMS), a presumed autoimmune disease, (9) and may reduce gadolinium-enhanced cerebral MRI lesions and proinflammatory tetanus toxoid-induced IFN-g and tumor necrosis factor-a (TNF-a) secretion in RRMS. (10) Stimulation tests are important in assessing residual b cell function in type 1 diabetes. (11) Therefore, we investigated whether ingested IFN-a could preserve residual b cell function for up to 1 year in patients treated within 1 month of diagnosis of type 1 diabetes mellitus in an open-label phase I clinical trial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because we detected changes in immune response and post hoc analysis suggested that the 10,000 IU dose may have an effect, ingested IFN-␣ received additional study in dose-response experiments in MS using biologic response markers (BRM). 21 Therefore, we examined MxA mRNA induction and TNF-␣ mRNA repression ex vivo to determine the optimal dose(s) of ingested IFN-␣ for future clinical trials in MS. We used IFN-␣ specifically because of the results from our animal and human experiments and its acid stability and not IFN-␤ because it has not shown bioactivity by mouth in humans. 22,23 …”
Section: Introductionmentioning
confidence: 99%